Optimisation of supercritical fluid extraction for fatty acids from Benincasa hispida seed oil: a response surface approach - Ramli, Rizal Za'im; Sarker, Md. Zaidul Islam; Ab. Hadi, Hazrina (IIUM Press, 2025)
Introduction: The goal of this study was the optimisation of the process parameters for the extraction of Benincasa hispida seed extract using the supercritical carbon dioxide. Methods: Response surface methodology was carried out using the design expert software with the implementation of process parameters including the temperature (40°C – 70°C), pressure (100 bar – 400 bar) and supercritical carbon dioxide flow rate (2 g/min – 10 g/min) in this study due to their significant impact towards the oil yield and the polyunsaturated fatty acids. Results: The optimised parameter for this supercritical fluid model is 70°C, 247 bar and 7 g/min while 0.36 bar and 40 °C has been chosen from previous studies as the optimised parameter for Soxhlet extraction. The oil yield (33% from Soxhlet extract and 9.67% from supercritical fluid extract) obtained was quite similar with previous studies, however, the polyunsaturated fatty acids obtained throughout this optimisation were much higher indicating that this study provided better output of the polyunsaturated fatty acids obtained from the seed oil. Moreover, the polyunsaturated fatty acids contents were also compared between the extract obtained from the conventional Soxhlet extraction versus novel supercritical fluid extraction techniques. Conclusion: The result shows the polyunsaturated fatty acids in the supercritical fluid extraction were significantly higher than the Soxhlet extraction due to the advantages and suitability of the polyunsaturated fatty acids extraction using the supercritical fluid extraction method